Shear Characteristics of Gravel Soil With Different Fillers - Zhang, Huahua; Luo, Yi; Yuan, Siyu; Zhou, Yuru; Zhou, Qiong; Zeng, Fanrong; Feng, Wei (Frontiers in Materials, 2022)
In recent years, China has established many large water conservancy projects in the western mountainous areas. Dam foundation excavation will produce a huge amount of waste rock mixture. The soil-rock mixture with unique structural characteristics is easy to cause geological disasters such as collapse, landslide, and debris flow under the earthquake, rainfall, and engineering disturbance. Therefore, research on the strength and shear characteristics of the soil-rock mixture is beneficial to avoiding soil-rock mixture disasters. In this paper, the soil-rock mixture in the slag dump site of Jinping Hydropower station is taken as the research object. The influence of different fillers on gravel soil shear characteristics is investigated through a large-scale triaxial test of coarse-grained soil. The slope stability of the slag dump site is analyzed using Midas GTS. Then, the most unfavorable sliding surface of the slag dump site is discovered, and the slope stability coefficient under the most unfavorable conditions is calculated. The results lay a scientific foundation for the design and construction of the slag dump slope.